Analisis kadar natrium benzoat pada kecap pedas yang beredar di pasaran dengan metode kromatografi lapis tipis (KLT) dan spektrofotometri Uv-Vis - Tamara Army; Ainil Fithri Pulungan; Ridwanto Ridwanto; Anny Sartika Daulay (Journal of Pharmaceutical and Sciences, 2023)
Sodium benzoate is one of the preservatives allowed in food and beverages. The objective of this research was to determine the level of sodium benzoate found in spicy soy sauce. Qualitative tests are first carried out on samples with the Thin Layer Chromatography (KLT) method, and quantitative tests are carried out using the spectrophotometry Uv-Vis method to determine the preservative level of sodium benzoate. Qualitative tests on KLT plates were carried out by optimising eluents (N-Butanol: Ethyl Acetate: Ammonia, Methanol: Ethyl Acetate: Ammonia, and Isopropanol: Ammonia), where the results of the three eluents showed that the Isopropanol: Ammonia eluents had Rf values from three samples that were close to each other with the comparison Rf values. The results of quantitative analysis on spectrophotometry Uv-Vis showed the total levels of Spicy Soy Sauce A 264.16±12.3206 mcg/g, Spicy Soy Sauce B 317.8±21.8643 mcg/g and Spicy Soy Sauce C 110.2±23.5356 mcg/g. Based on these results, it can be concluded that sodium benzoate levels in samples A, B, and C meet the requirements of the maximum usage limit standard, which is not more than 600 mg/kg.